2021
DOI: 10.1111/jfpp.15394
|View full text |Cite
|
Sign up to set email alerts
|

Development of slow melting dietary fiber‐enriched ice cream formulation using bacterial cellulose and inulin

Abstract: Effect of addition of bacterial cellulose (BC) and inulin on properties such as melting rate, over run, and sensory properties of ice cream was investigated. BC-supplemented ice creams were characterized by a significant reduction in the melting rate, while inulin contributed to enhance the over run and sensory properties. Sensory perceptions varied for BC at 17% and 30% (wet weight) when compared to inulin addition at 0.7% and 1.4% (dry weight). Eight formulations of ice cream were prepared, varying inulin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…Increasing BPP and CP mixed powders increased the melting rate. This finding is insinuated and revealed that the addition of fiber powder into an ice cream matrix can increase thermal diffusion when the product is exposed to the environment and absorbs heat 24 , 25 . Moreover, the overrun in this research was found to be in the same direction as the melting rate.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing BPP and CP mixed powders increased the melting rate. This finding is insinuated and revealed that the addition of fiber powder into an ice cream matrix can increase thermal diffusion when the product is exposed to the environment and absorbs heat 24 , 25 . Moreover, the overrun in this research was found to be in the same direction as the melting rate.…”
Section: Resultsmentioning
confidence: 99%
“…Düşük kalorili dondurmalarda yağ ikame maddesi olarak BC kullanımının tekstürün iyileştirilmesine, erime direnci ve viskozitenin artırılmasına, sıcaklık değişimleri esnasında şeklin korunmasına katkı sağladığı bildirilmektedir. Gluconacetobacter xylinus' dan elde edilen selüloz ile inulinin dondurmada erime oranı, hacim artışı ve duyusal nitelikler üzerine etkisi araştırılmış ve pozitif etkiye sahip olduğu belirlenmiştir [54]. Guo ve ark.…”
Section: Mikrobiyel Selülozlarunclassified
“…At the same time, free water present in the mix freezes with the formation of ice crystals, which form an exceptional and desirable texture of ice cream [ 2 , 3 ]. In the case of the formation of large ice crystals, the sensory properties of ice cream deteriorate significantly [ 4 ], which requires control of the process of crystallization of free water during production and storage of the finished product. The recommended size range of ice crystals in ice cream should be within 20–50 μm [ 5 ], but the formation of ice crystals with a size of 10 to 20 μm is an important condition for giving the product a creamy consistency [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%